The Need for Palliative Care in Primary Health Care - Nita Arisanti; Dany Hilmanto; Elsa Pudji Setiawati; Veranita Pandia (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2018)
.................... The access to palliative care in ends of life is one of the patients’ rights. Therefore it should be delivered into every level of health care for patients and family members. In some countries, palliative care is more frequent delivered in hospitals compare to primary health care, even though primary health care has a significant role in providing palliative care. Most families prefer to care for patients at home rather than in the hospital................................... The implementation of palliative care in Indonesia is still very limited to certain hospitals, even though doctors in primary care have great potential to offer such care to people in the community. Some of the factors contributing to the implementation are cultural and socioeconomic factors, patient and family perceptions, attitudes of service providers, lack of trained personnel, distribution of palliative care units, lack of consolidation and limited funds. As a result, patients with end-stage disease die in hospitals without receiving palliative care or dying at home with inadequate support................